Utilization Of Carbon Waste Leaf As A Organic Pigment In Whiteboard Spidol Ink - Andya Satya Purnomo Putro; Arnetha I Putri; Rizka Nur'ain; Jasmine S.S. Arum (Jurnal Fisika FLUX, 2018)
Waste has become one of the problems that until now has not been resolved in the community. One type of waste that is abundant is organic waste in the form of leaves. Based on this fact which demands a creative and innovative way of processing waste into a powerful product. One effort made is the utilization of leaf waste as organic color pigment on white board marker ink. Pigment is obtained by reducing leaf waste to homogeneous form of carbon powder that is burning leaf garbage in low oxygen condition then done simple mixing process with other material of ink maker. The resulting ink is tested for transmittance in carbon mass variations in the range from 1 to 6 grams, the results show that the more carbon mass, the lower the intensity of the light passes. The absorption rate test shows that the carbon inks have a speed similar to the ink type on the market, which is 0.081 mm / s. When the performance test of the carbon ink on the white board shows almost the same result of black with commercial ink and can adhere well so it is suitable if applied as white board marker ink.